Fibrin network pattern changes of platelet-rich fibrin in young versus old age group of individuals: A cell block cytology study - Shravanthi Raghav Yajamanya; Anirban Chatterjee; Chaitanya Nischay Babu; Deepika Karunanithi (Wolters Kluwer Medknow Publications, 2016)
Background: To evaluate variations in fibrin network patterns of the platelet-rich fibrin (PRF) in different age groups. Materials and Methods: Ninety-five patients were divided into three age groups: Group 1: (20-39 years); Group 2: (40-59 years); and Group 3: (60 years and above). PRF was prepared from blood samples of all patients and were subjected to cell block cytology method of histological analysis and slides were prepared to histologically assess the age-related changes in (i) fibrin network patterns in terms of density and (ii) entrapment of platelets and white blood cells (WBCs) within fibrin meshwork. Results: Two types of fibrin network pattern arrangements noticed: Dense and loose types in three age groups. However, there was a noticeable decrease in the dense type of fibrin network with progressing age and increase in the loose type of fibrin arrangement. Furthermore, variation in a number of platelets and WBCs entrapped within fibrin network in relation to age was noticed. Conclusion: From the current study it can be concluded that age can be considered as one of the influencing factors on quality of PRF in terms of fibrin network patterns and hence, platelet and WBCs entrapment within these fibrin networks.